A Literary and Social Depiction of an Indian City: "Masala" Eroticism and Perverse Realism in Raj Rao’s BomGay - García-Arroyo, Ana (Complutense Journal of English Studies, 2018)
BomGay is the major stage that the Indian English writer Raj Rao chooses in his literary work to represent the gay performances in Bombay. BomGay becomes an epitome of gay culture in India, which has to find its own (in)visible ways to survive, even today, when the oppressive section of the Indian Penal Code, 377, is still used to punish those who express their alternative sexualities. This paper examines the rich artistic performances of the gay underworld narrated in Rao’s fictional city of BomGay that accurately envision a particular face of urban India. Firstly, I will focus on how the picture of unpleasantness and nastiness of the Indian masses is depicted as erotically natural in Rao’s fiction. I will study the two major factors that always converge in the portrayal of the microcosm of BomGay, scatology and (homo)sexual explicitness, which provide the foundations for Rao’s erotic realism, in order to combat hegemonic discourse and social oppression.